Answer:
X-intercept = -3 and y-intercept = 6
Step-by-step explanation:
We can start off by isolating the y term. To do that, we must add 2y to both sides to get
![4x=2y-12](https://tex.z-dn.net/?f=4x%3D2y-12)
Now, we must add 12 to both sides and the y term will be all alone on the right side:
![4x+12=2y](https://tex.z-dn.net/?f=4x%2B12%3D2y)
Now, to have only y on the right side, we must divide by 2 to get:
![y=2x+6](https://tex.z-dn.net/?f=y%3D2x%2B6)
In slope-intercept form, b is the y-intercept, and 'b' in this equation is 6. We have our y-intercept.
To find our x-intercept, y must be equal to zero. We can plug in that value for y and solve for x:
![0=2x+6](https://tex.z-dn.net/?f=0%3D2x%2B6)
We can start off by subtracting 6 from both sides to get:
![2x=-6](https://tex.z-dn.net/?f=2x%3D-6)
We can then divide both sides to get
when y is equal to 0. Thus, we have our x-intercept.